SYNTHEZISING IDEOLOGY: REPRESENTATION OF AFRICAN-AMERICANS IDENTITY IN THE 1960S - Ida Rochani Adi (Celt: A Journal of Culture, English Language Teaching & Literature, 2014)
Identity is shaped through values and values are maintained through ideology. Ideology is therefore important for every nation in making its vision into realization. The research is intended to find out (1) the values that African-American would like to fight for, through which they try to create their own identity, (2) how African-Americans, as minority, tried to build their identity in 1960s, and (3) the common ground of the effort in sustaining their ideology in that they can build their identity. This is a qualitative and interdisciplinary research in the constructivist paradigm in which qualitative method is used in gathering the data and descriptive qualitative is used in analyzing the data. This research reveals that the ways in establishing the African-American identities are through sports, social practices and music. In relation to the notion of ideology, the spreading and strengthening of African-American ideology, both cultural and psudo ideology, are done through humanitarian actions to fight the discrimination they endure. This research determines that the synthesis in creating identity among the whites is through individual freedom and responsibility in which freedom is the common ground of human existence marking the primary force of the existence of identity.